Glucocorticoid influence on prognosis of idiopathic sudden sensorineural hearing loss - Bogaz,Eduardo Amaro (2014)
INTRODUCTION: Idiopathic Sudden Sensorineural Hearing Loss (ISSHL) is defined when a loss of at least 30 dB occurs in over 3 continuous frequencies, in up to 72 hours, of which etiology is not established, despite adequate investigation. Different types of treatment regimens have been proposed, but only glucocorticoids have shown some evidence of benefit in the literature. OBJECTIVE: To analyze whether the type of treatment or time of treatment with glucocorticoids have any influence on hearing recovery in ISSHL. METHODS: Observational retrospective cohort study. One hundred twenty-seven patients with ISSHL, treated at outpatient clinics between the years 2000 and 2010, were studied. We evaluated the prognostic correlation of the type of treatment and time to treatment with glucocorticoids and ISSHL. RESULTS: The absolute hearing gain and the relative hearing gain was as follows: 23.6 dB and 37.2%. Complete recovery was observed in 15.7% of patients, significant recovery in 27.6% and recovery in 57.5%. CONCLUSION: In this study, there was no difference between the use and nonuse of glucocorticoids in hearing improvement. However, when started within seven days after onset, the use of glucocorticoids was a factor of better prognosis.